The effectiveness of case-based concept map to improve pathophysiology knowledge and critical thinking among first-year nursing students: a quasi-experimental study - Pratiwi, Hikmi Muharromah; Nani, Desiyani; Saryono, Saryono; Cakrawati, Laxmi Mustika (Jurnal Ners, 2024)
Introduction: Improving pathophysiology knowledge and critical thinking skills of nursing students remains as a challenge faced by nursing educators. Thus, an innovative learning method is required. Concept map by adding cases might assist increasing students' pathophysiology knowledge and critical thinking skills. Methods: A quasi-experimental study with pre- and post-test with control group design involved 104 first-year nursing students of Universitas Jenderal Soedirman, Purwokerto, Central Java in April-June 2023. Participants were divided into two classes at the beginning of the first semester and randomly allocated into the intervention (54 respondents) and the control (50 respondents) group. The intervention group was provided typical learning added with a case-based concept map development weekly for 7 weeks, while the control group underwent regular lectures based on the syllabus. Pathophysiology knowledge was measured by using Multiple Choice Questions, while critical thinking was evaluated by using the Critical Thinking Disposition Inventory questionnaire. Independent-t test and paired test were applied to evaluate the effectiveness of implementing the case-based concept map. Results: The mean score for knowledge the pathophysiology of the disease in the intervention group was significantly higher than the those in the control group (t=5.24, p=0.000). However, there was no difference in the average scores of critical thinking between two groups discovered in the study (t=0.90, p=0.37). Conclusions: Case-based concept map can be recommended as an innovative and effective learning method for teaching disease pathophysiology to nursing students. However, the case-based concept map in this study is still not consistent in improving students' critical thinking skills.